Pantun in the classical and Digital Malay Era: A phenomenological study - Nur, Hidayatun; Suwandi, Sarwiji; Wardani, Nugraheni Eko (Research Journal in Advanced Humanities, 2024)
This study aims to describe the function of Pantun in the Classical Malay era and the digital era in Malay society in Riau Province, Indonesia. This research is descriptive qualitative research using a phenomenological strategy. Data were collected by interview techniques, namely with humanists, chanters, and Pantun maestros, and then through documentation and observation. Pantun data was taken from representatives of the four major rivers in Riau: the Rokan, Siak, Kampar, and Indragiri. The validation of the research data was carried out using source triangulation. Data analysis was done using interactive techniques: data reduction, presentation, analysis, and conclusion. The results of this study indicate that the function of Pantun in Riau in the Classical Malay era was the function of communication in daily life, in traditional wedding processions and conveying feelings of affection, didactic functions, entertainment functions, and Kamal functions. The function of Pantun in Riau in the digital era is only to open and close remarks at an event, such as in traditional wedding processions and performing arts entertainment.